Subduction or sagduction? Ambiguity in constraining the origin of ultramafic-mafic bodies in the Archean crust of NW Scotland - Johnson, Tim E.; Brown, Michael; Goodenough, Kathryn M.; Clark, Chris; Kinny, Peter D.; White, Richard William (Precambrian Research, 2016)
The Lewisian Complex of NW Scotland is a fragment of the North Atlantic Craton. It comprises mostly Archean tonalite-trondhjemite-granodiorite (TTG) orthogneisses that were variably metamorphosed and reworked in the late Neoarchean to Paleoproterozoic. Within the granulite facies central region of the mainland Lewisian Complex, discontinuous belts composed of ultramafic-mafic rocks and structurally overlying garnet-biotite gneiss (brown gneiss) are spatially associated with steeply-inclined amphibolite fades shear zones that have been interpreted as terrane boundaries. Interpretation of the primary chemical composition of these rocks is complicated by partial melting and melt loss during granulite facies metamorphism, and contamination with melts derived from the adjacent migmatitic TTG host rocks. Notwithstanding, the composition of the layered ultramafic-mafic rocks is suggestive of a protolith formed by differentiation of tholeiitic magma, where the ultramafic portions of these bodies represent the metamorphosed cumulates and the mafic portions the metamorphosed fractionated liquids. Although the composition of the brown gneiss does not clearly discriminate the protolith, it most likely represents a metamorphosed sedimentary or volcano-sedimentary sequence. For Archean rocks, particularly those metamorphosed to granulite facies, the geochemical characteristics typically used for discrimination of paleotectonic environments are neither strictly appropriate nor clearly diagnostic. Many of the rocks in the Lewisian Complex have 'arc-like' trace element signatures. These signatures are interpreted to reflect derivation from hydrated enriched mantle and, in the case of the TTG gneisses, partial melting of amphibolite source rocks containing garnet and a Ti-rich phase, probably rutile. However, it is becoming increasingly recognised that in Archean rocks such signatures may not be unique to a subduction environment but may relate to processes such as delamination and dripping. Consequently, it is unclear whether ...